Self-Control Strategies Among Adults in Overcoming Online Gambling Addiction: A Qualitative Study - Agustini, Wahyunnisa Aisy; Purnomosidi, Faqih (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: In the continuously evolving digital era, access to the internet provides both numerous benefits and challenges for society. One of the significant challenges is the widespread practice of online gambling, which has become increasingly accessible to various groups, including adults. This study aims to analyze the self-control strategies applied by adults in Cirebon Regency to overcome online gambling addiction. Research Methods: The research method used is qualitative, with in-depth interviews conducted with seven respondents. Finding/Results: The results show that self-control is exercised through three main aspects: behavioral control, cognitive control, and decision-making. Behavioral control involves actions to avoid environments that trigger the desire to gamble and replace them with positive activities, such as working, praying, or maintaining healthy family relationships. Cognitive control is carried out by gathering information about the negative impacts of online gambling through personal experiences and electronic media, helping respondents understand the risks and harms of gambling. Decision-making based on moral and spiritual values becomes a key factor in considering the actions taken, such as drawing closer to God to strengthen mental resilience and choosing more beneficial activities. Conclusion: This study highlights that overcoming online gambling addiction requires a holistic self-regulation strategy that integrates behavioral modification, cognitive awareness, and value-based decision-making.